What are the implications of stellar chemical abundances in dwarf galaxies?. Issue Volume 14:Issue S344(2019) (August 2018) - Suda, Takuma; Aoki, Wako; Katsuta, Yutaka; Yamada, Shimako; Matsuno, Tadafumi; Iwata, Saku; Takei, Yuki; Fujimoto, Masayuki Y.
Abstract: We analyse the chemical abundances of stars in the local group dwarf galaxies using the SAGA database. The inspection of the relationship between Eu and Ba abundances confirms an anomalously Ba-rich population in Fornax, which indicates a pre-enrichment of interstellar gas with r -process elements.